Walkability index and ridership of the Bus Rapid Transit (BRT) line stations in Malaysia - Thevadass, Hamsareka (2023)
This project aims to investigate the existing conditions of walking environment around the Bus Rapid Transit (BRT) Sunway Line stations in Malaysia by establishing Walkability Index specifically to evaluate walking environment around the stations and identifying mitigation measures by producing a travel mode shift model based on the perspective of potential BRT commuters around the stations. However, the walking environment in the BRT catchment area were barely assessed. Hence, this study develops a visual assessment to assess the walking environment around BRT and it is then computed to develop the Walkability Index for the BRT stations to understand the current performance where a set of parameters were created and a Visual Assessment Form which is intended to assess the walkways, junctions and BRT stations. The commuter’s perception and expectation were also considered as an additional weight in computing the Walkability Index. This research also provides an in-depth consideration on travel mode shift from using private transport to using public transport, especially advocating for the active transportation as the mode of choice, where a forecasting model to predict the likelihood of an individual of using BRT by investigating the commuters’ travel mode choice behaviors.